2012
DOI: 10.1002/adfm.201201090
|View full text |Cite
|
Sign up to set email alerts
|

Making a Robust Interfacial Scaffold: Bijel Rheology and its Link to Processability

Abstract: Confocal microscopy and rheology studies of two bijel systems are presented to elucidate relationships between the physicochemical properties of bijels and their ability to be utilized as soft matter templates for materials synthesis. For the first time, the origins of viscoelasticity in these systems are investigated using conventional rheometry and a direct correspondence between the elastic storage modulus, particle loading, and the departure from criticality is observed. Further, the rheological transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 26 publications
6
121
0
Order By: Relevance
“…The asymmetric drop shape evolution strongly suggests that the suspension is viscoelastic, which we attribute to the gelation and interfacial attachment of nanoparticles. [ 29 ] These droplets form complex shaped bijel microparticles of nonuniform lengths as they fl ow through the device. To better regulate drop pinch off, control over the suspension wetting on the inner capillary is critical, and is achieved by coating the capillary with a cationic polyelectrolyte, poly(diallyldimethylammonium chloride).…”
Section: Doi: 101002/adma201503509mentioning
confidence: 99%
“…The asymmetric drop shape evolution strongly suggests that the suspension is viscoelastic, which we attribute to the gelation and interfacial attachment of nanoparticles. [ 29 ] These droplets form complex shaped bijel microparticles of nonuniform lengths as they fl ow through the device. To better regulate drop pinch off, control over the suspension wetting on the inner capillary is critical, and is achieved by coating the capillary with a cationic polyelectrolyte, poly(diallyldimethylammonium chloride).…”
Section: Doi: 101002/adma201503509mentioning
confidence: 99%
“…We also found that the particle framework formed at the interface maintains even after the PS/PB phases are re-mixed. Although this so-called ''monogel'' structure has been reported in polar bijels, 18,20 we argue that the formation of a particle framework in nonpolar bijels arises from the nonpolar nature of particle-matrix and inter-particle interactions.…”
Section: Introductionmentioning
confidence: 98%
“…In froth flotation for example, the adsorption of particles is exploited for mineral extraction [4]. More recently particle assembly at fluid interfaces has been studied as a platform for the design of novel colloid-based materials [5][6][7][8][9][10][11][12][13]. In addition, the interaction between particles and fluid interfaces is important for the field of lab-on-a-chip biosensing, where particles are used for their large surface-to volume ratio, flexible bio-functionalization, stability, and for their actuation and detection properties (see e.g.…”
mentioning
confidence: 99%